Efeitos da derivação duodeno-jejunal sobre o metabolismo lipídico hepático e morfologia das ilhotas pancreáticas em ratos com obesidade hipotalâmica - Cantelli, Kathia Regina (2015)
Purpose: Herein we evaluated the expression of genes and protein involved with hepatic lipids pathway and investigate whether the improvement on glucose homeostasis is associated with modifications in the islets morphology in HyO rats submitted to duodenal-jejunal bypass (DJB). Methods: During the first 5 days of life, male newborn Wistar rats received a subcutaneous injection of monosodium glutamate [4 g/kg body weight (BW), hypothalamic obesity (HyO) group], or saline (CTL group). At 90 days of age, HyO rats were submitted to DJB or sham operations forming HyO DJB and HyO Sham group, respectively. Two months after DJB, serum parameters, expression of genes and protein in the liver and islets morphology were verified. Results: Although DJB operation normalized serum triglycerides (TG) and non-esterified fatty acids (NEFA) concentration compared to HyO Sham rats, HyO DJB rats did not alter TG liver content as well as, the expression of hepatic genes and protein involved with lipids metabolism. DJB operation normalized insulinemia and insulin resistance and restored β-cell secretion in the presence of 8.3 mM glucose independently of weight loss. In addition, HyO DJB rats presented a reduction in total islets and β-cell area (pancreas area percentage) and in islets cells proliferation (verified by the number of nucleus stained by Ki67 protein - a cellular marker for proliferation). Conclusions: Although DJB not affect liver lipids metabolism in HyO rats two months after surgery, the improvement on glucose homeostasis could be associated with modifications in islets morphology and proliferation.